Marketing Strategy for MSME Management Students at Pamulang University During the Covid-19 Pandemic - Harsono, Yhonanda; Permada, Dewi Nari Ratih; Munarsih, Munarsih (Journal Socio Humanities Review, 2022)
The purpose of this study was to determine product innovation strategies in increasing sales to Pamulang University Management Student MSMEs during the Covid-19 Pandemic, to determine promotional strategies in increasing sales of Pamulang University Management Student MSME products during the Covid-19 Pandemic and to find out strategies product quality in increasing sales at Pamulang University Management Student MSMEs during the Covid-19 Pandemic. This study used a qualitative descriptive research method. After doing the research it was found that the product innovation strategy in increasing sales through creating products with different products in general and having a unique brand or product brand that attracts consumers, Promotional strategies in increasing sales are through online marketing or social media, such as: Instagram, Facebook, WhatsApp, etc. as well as through various social media platforms that can be accessed by all people, especially the Indonesian people. Furthermore, the product quality strategy in increasing sales at Pamulang University Management Student MSMEs during the Covid-19 Pandemic is to improve product quality, service through social media admins to deal with online consumers. And there are bonuses for consumers, such as free masks, discounted prices and free shipping. Furthermore, the product quality strategy in increasing sales at Pamulang University Management Student MSMEs during the Covid-19 Pandemic is to improve product quality, service through social media admins to handle online consumers. And there are bonuses for consumers, such as free masks, discounted prices and free shipping. Furthermore, the product quality strategy in increasing sales at Pamulang University Management Student MSMEs during the Covid-19 Pandemic is to improve product quality, service through social media admins to deal with online consumers. And there are bonuses for consumers, such as free masks, discounted prices and free shipping.